2020
DOI: 10.3390/microorganisms8111825
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Association with Toxin Determinants in Clostridium perfringens Isolates from Chickens

Abstract: The aim of the present study was to investigate variation in antimicrobial resistance in Clostridium perfringens (C. perfringens) isolated from chickens after withdrawal of antimicrobial growth promoters (AGPs); and to investigate the correlation between the presence of toxin genes (cpb2, netB, and tpeL) and antimicrobial resistance. Altogether, 162 isolates of C. perfringens were obtained from chickens displaying clinical signs of necrotic enteritis (n = 65) and from healthy chickens (n = 97) in Korea during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
4
15
0
Order By: Relevance
“…This might refer to the presence of other mechanisms exhibited by the bacterium for resistance against erythromycin. The findings of resistance to Tetracycline and Erythromycin are consistent with (35) who reported resistance of C. perfringens isolates to these two antibiotics by 50.8 and 29.2 %, respectively. However, our finding may not agree with 36, who reported that the most probable mechanism of resistance against macrolides is modifying a target site by a methylase encoded by the ermB gene.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This might refer to the presence of other mechanisms exhibited by the bacterium for resistance against erythromycin. The findings of resistance to Tetracycline and Erythromycin are consistent with (35) who reported resistance of C. perfringens isolates to these two antibiotics by 50.8 and 29.2 %, respectively. However, our finding may not agree with 36, who reported that the most probable mechanism of resistance against macrolides is modifying a target site by a methylase encoded by the ermB gene.…”
Section: Resultssupporting
confidence: 90%
“…However, tpeL toxin might contribute to the antimicrobial resistance as it was detected in about 40 % of the resistant isolates. Although this hypothesis needs more in-depth investigations, it could be in agreement with (35) who reported that the tpeL gene was more common among C. perfringens isolates susceptible to tetracycline. From our previous studies, it could be stated that the antimicrobial resistance profiles of C. perfringens varies significantly according to sources, coun-tries, other bacterial factors rather than the resistance-driving genes.…”
Section: Resultssupporting
confidence: 86%
“…Moderate (18.5%) to high (65%) resistance levels were observed for bacitracin, whereas penicillin and amoxicillin resistance was rare with proportions of only 0% and 9% being reported by Wei et al. ( 2020 ) and Mwangi et al. ( 2019 ).…”
Section: Assessmentmentioning
confidence: 89%
“…All three studies found high levels (50.8-62%) of resistance to tetracycline. Moderate (18.5%) to high (65%) resistance levels were observed for bacitracin, whereas penicillin and amoxicillin resistance was rare with proportions of only 0% and 9% being reported by Wei et al (2020) and Mwangi et al (2019). The proportion of resistance to erythromycin was either very low (2%; Slavic et al (2011)) or moderate (29.2%; Wei et al (2020)).…”
Section: Chickensmentioning
confidence: 98%
“…However, the widespread use of antibiotics leads to the spread of antibiotic-resistance genes in bacteria in the environment. C. perfringens strains have been found to be resistant to medically important antibiotics for humans: tetracycline, virginiamycin, penicillin, clindamycin, vancomycin, ceftriaxone, and erythromycin ( Slavic et al, 2011 ; Wei et al, 2020 ). Besides, C. perfringens has been found to be resistant to bacitracin ( Slavic et al, 2011 ), a narrow-spectrum antibiotic used to prevent and control NE, increase rate of weight gain and improve feed efficiency in the poultry industry ( Prescott et al, 1978 ).…”
Section: Introductionmentioning
confidence: 99%